Binormal and complex symmetric weighted composition operators on the Fock Space over C - Santhoshkumar, C. (Matematychni Studii, 2023)
In this paper, we give simple characterization of binormal weighted composition operators C_ψ, φ on the Fock space over C where weight function is of the form ψ(ζ) = e^ζ, c for some c C. We derive conditions for C_φ to be binormal such that C^*_φC_φ and C^*_φ + C_φ commute. Finally we give some simple characterization of binormal weighted composition operator to be complex symmetric.